An Innovative Idea for Reducing the Musculoskeletal Disorders in Drywall Installation. (September 2013) - Sengupta, Priyadarshini Dasgupta; Punnett, Laura; Moir, Susan; Kuhn, Sarah; Buchholz, Bryan
Objective: The study was conducted to assess an intervention suggested by the workers to reduce the ergonomic exposures of the drywall installation task. Methods: At several focus group meetings the drywall installers were asked to brainstorm on innovative ideas that could reduce their ergonomic/musculoskeletal exposures during the drywall installation work. The workers discussed the idea of using a 'deadman' (long narrow piece of sheetrock) to help hold the panels on the ceiling while installing them. The researcher collected quantitative exposure data (PATH, 3DSSPP) at the baseline and intervention phases. The data at the two time periods were compared to find out any change in the exposure with use of the 'deadman'. Results: Results showed that exposures (such as overhead arm and awkward trunk postures and heavy load handling) were reduced in the intervention phase while using an electrical lift and the 'deadman'. Conclusion: The concept of the 'deadman', which was shown to help reduce musculoskeletal exposures during ceiling installation, can be used to fabricate a permanent ergonomic tool to support the ceiling sheetrock.